Construction of a mycelium sphere using a Fusarium strain isolate and Chlorella sp. for polyacrylamide biodegradation and inorganic carbon fixation - Zhang, Huichao; Shangguan, Mohan; Zhou, Chang; Peng, Zhaoyang; An, Zhongyi (Frontiers in Microbiology, 2023)
In the context of global demand for carbon reduction, the formation of inorganic carbon (IC) in the wastewater from oil flooding becomes a potential threat. In this study, Chlorella sp. and Fusarium sp. were used to assemble a fungal-algal pellet to degrade polyacrylamide (PAM) and fix IC in synthetic oil-flooding wastewater. The results showed that the combination of Chlorella sp. and Fusarium sp. was more effective at degrading PAM and removing carbon than a monoculture. With PAM as the sole nitrogen source, the degradation of PAM by the consortium was enhanced up to 35.17±0.86% and 21.63±2.23% compared with the monocultures of fungi or microalgae, respectively. The degradation of the consortium was significantly enhanced by the addition of an external nitrogen source by up to 27.17±2.27% and 22.86±2.4% compared with the monoculture of fungi or microalgae, respectively. This may depend on the effect of synergy between the two species. For the removal of IC from the water, the removal efficiency of the consortium was higher than that of the microalgae by 38.5±0.08%, which may be attributed to the ability of the fungi to aid in the adsorption of nutrients and its assimilation by the microalgae. Therefore, the Fusarium-Chlorella consortium can effectively degrade PAM, while simultaneously fixing carbon, which provides a feasible scheme for the treatment and carbon neutralization of the wastewater that contains PAM.